Assessment of anemia in cases of acute myocardial infarction in a tertiary care hospital in central India - Thakur, Aditya; Peepre, Kunal; Pendro, Budhram; Dhakar, Jagmohan Singh; Singh, Tej Pratap; Lalu, Aryasree (International Journal Of Community Medicine And Public Health, 2024)
Background: Anemia is a known risk factor for ischemic heart disease and heart failure. It is also associated with increased mortality in acute myocardial infarction (AMI) patients. The study aimed to determine the anemia status of AMI patients and educate them on anemia and its impact on health. Methods: This was cross-sectional study conducted among 100 AMI patients admitted to ICCU of Hamidia hospital, Bhopal over 2 months. Haemoglobin levels were recorded and patients classified as non-anemic, mildly, moderately or severely anemic based on WHO criteria. Patients’ sociodemographic profile and risk factors also collected. Results: Of the 100 patients (mean age 55.6 years), 76% were males. 88% patients had anemia-74% mild, 13% moderate and 1% severe. The 30-45 years age group reported the highest frequency of mild anemia cases (20 out of 31). Absence of anemia was highest among the younger <30 years group (9 out of 31). Anemia was higher in females, Patient with vegetarian diet had comparatively more anemia than the patient consuming mixed diet. Conclusions: A high prevalence of anemia was found among AMI patients. Counselling can help improve health by increasing awareness of anemia management. Screening AMI patients for anemia and therapeutic interventions were recommended.